1988
DOI: 10.1159/000293769
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Fetal Heart Rate Variability by Spectral Analysis in Growth-Retarded Fetuses

Abstract: The analysis of short-term variability of fetal heart rate in the frequency domain was performed. The fetal activity states (quiescence, trunk rotation, body movements, fetal breathing movements) were taken into account. The differences between the shapes of power spectra in physiological and growth-retarded fetuses were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
1
8
0
3
Order By: Relevance
“…As the frequency components, corresponding to the normal physiological mechanisms of the FHR, have been identified, any deviations in the power spectra could be an indication of pathology. In previous studies a differentiation in the power spectra of FHR variability in pregnancies complicated by diabetes mellitus (Ropacka et al, 2000), IUGR (Breborowicz et al, 1988;Ropacka et al, 2000), hypertension and hypoxia (Oppenheimer and Lewinsky, 1994;Rassi and Lewis, 1995) has been reported. In this study we did not observe any deviation in the spectra that could be correlated with an unfavorable pregnancy outcome (Table 1).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As the frequency components, corresponding to the normal physiological mechanisms of the FHR, have been identified, any deviations in the power spectra could be an indication of pathology. In previous studies a differentiation in the power spectra of FHR variability in pregnancies complicated by diabetes mellitus (Ropacka et al, 2000), IUGR (Breborowicz et al, 1988;Ropacka et al, 2000), hypertension and hypoxia (Oppenheimer and Lewinsky, 1994;Rassi and Lewis, 1995) has been reported. In this study we did not observe any deviation in the spectra that could be correlated with an unfavorable pregnancy outcome (Table 1).…”
Section: Discussionmentioning
confidence: 84%
“…Analysis of the frequency content at various stages of gestation provides information on the fetal sympathovagal balance and assesses the fetal growth and development. Pathological conditions such as diabetes mellitus, intrauterine growth retardation, hypertension and hypoxia that could possibly affect FHR might also influence power spectra (Oppenheimer and Lewinsky, 1994;Rassi and Lewis, 1995;Breborowicz et al, 1988;Ropacka et al, 2000). The frequency components were identified in two bands: one high frequency band (HF), between 0·15 and 0·4 Hz, around the respiratory frequency (RSA) and one low frequency band (LF) between 0·04 and 0·15 Hz, which is mediated by the sympathetic system and is attributed to Mayer waves.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, gestational age showed no association with low‐frequency or total fetal heart rate variability probably because only pregnancies over 35 weeks were included. Fetal movements may increase low‐frequency fetal heart rate variability, but there have also been contradictory results 24,25 . During delivery, fetal movements decrease and, when they do occur, they are mostly associated with uterine contractions 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…We measured umbilical and uterine flow velocity waveforms at 10 -20 weeks of gestation to determine both maternal and fetal heart rate variability and flow velocity variability as parameters of functional control of the autonomic nervous system 12 . The aim of the study was to establish maternal and fetal variability in heart rate and blood flow velocity to compare developing and mature systems for autonomic regulation of cardiovascular function.…”
Section: Introductionmentioning
confidence: 99%